Functional Performance For Patients Post Heart's Valves Replacement at Cardiac Surgery Centers in Baghdad City - Atiea, Jabbar; Kadhum, Halima (Iraqi National Journal of Nursing Specialties, 2018)
AbstractObjectives: The study is carried out to assess functional performance for heart's valve replacement patients and find out relationship with sociodemographic data and clinical data Methodology: Descriptive design is carried out at cardiac surgery centers in Baghdad ; Ibn -Al Betar Specialized for cardiac surgery center and Al-Iraqi center for cardiac disease. its initiation from December28the 2013 to September 1st 2014,A non- probability (purposive) sample of 50 adults patients are attended cardiac surgery centers at Baghdad city and who have heart valves replacement. The data collection through development of questionnaire which is composed from three parts(socio demographic data, clinical information, functional performance) after validity and reliability , validity has been determined through (15) experts and reliability has been determined through pilot study, The data are descriptive statistical and analysis through application of descriptive and inferential statistical methods.Results: The result of the study has revealed that level of Functional Performance for the patients post heart's valve replacement were(80%) moderate and (20%)low majority of the study samples (92%)have regular up take of the anticoagulation drugs and majority of the samples(92%) have mechanical valve implementation ,The results of the study represent a significant statistical correlation between the level of Functional Performance for patients post heart's valve replacement group and the age p=0.042* , level education p=0.008*, socio economic status p=0.004*, ejection fraction p=0.044* ,follow up of the patients p=0.042* , regular up take of the anticoagulation drugs p=0.004*, mechanical valve used p=0.05*, duration post operation p=0.044*Recommendations : The study recommended to using biologic valve (tissue valve) for elderly patient instead mechanical valve when valve replacement to reduce complication anticoagulation drugs and enhance survival post operation, establishing Psychological consultation to copy the patients with emotional and social impact which results from the operation, an education program should be designed to increase patients education about self-care and increase satisfaction with care ,use education and training programs (regular lectures for nursing staff) to improving the expertise and knowledge of nurses to play an essential role in fostering patients care and prevent valve infection.